Philosophy of Approaches in Social Sciences: A Review of Positivism, Phenomenology and Critical Social Sciences in Qualitative Research - Mathotaarachchi, K. P.; Thilakarathna, K. A. A. N. (Technium Social Sciences Journal, 2021)
Qualitative approach so as to speak has become one of the most utilized methodologies when it comes to studies that have been conducted in the realm of social science. While this being said, when compared to the quantitative approach, qualitative studies focus more on the textual articulation of the study than with empiricism. In this context, it often uses many of the already established theories in proceeding with its studies. This paper in particular examines how qualitative studies are conducted under the philosophical underpinnings rooted in positivism, phenomenology and critical social science.